2021
DOI: 10.1038/s41598-021-00143-7
|View full text |Cite
|
Sign up to set email alerts
|

Little evidence for sex or ovarian hormone influences on affective variability

Abstract: Women were historically excluded from research participation partly due to the assumption that ovarian hormone fluctuations lead to variation, especially in emotion, that could not be experimentally controlled. Although challenged in principle and practice, relevant empirical data are limited by single measurement occasions. The current paper fills this knowledge gap using data from a 75-day intensive longitudinal study. Three indices of daily affective variability—volatility, emotional inertia, and cyclicity—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 66 publications
(80 reference statements)
0
8
0
1
Order By: Relevance
“…Our results also debunk the myth that female variability is predictive of the importance of the estrous cycle for the regulation of the outcome of interest. This frequently touted misconception states that it is now proven that the estrous and menstrual cycles do not make females more variable than males, and that this means that (a) females deserve to be studied and that (b) ovarian cycles are not important experimental considerations [24,46,47]. First, we show that it is possible to not find any difference in the variability between males and females, and still find an effect of the estrous cycle.…”
Section: The Estrous Cycle Tracking Is a Stressor And May Represent A...mentioning
confidence: 59%
“…Our results also debunk the myth that female variability is predictive of the importance of the estrous cycle for the regulation of the outcome of interest. This frequently touted misconception states that it is now proven that the estrous and menstrual cycles do not make females more variable than males, and that this means that (a) females deserve to be studied and that (b) ovarian cycles are not important experimental considerations [24,46,47]. First, we show that it is possible to not find any difference in the variability between males and females, and still find an effect of the estrous cycle.…”
Section: The Estrous Cycle Tracking Is a Stressor And May Represent A...mentioning
confidence: 59%
“…Research suggests that, although men and women tend to have similar emotional reactivity and fluctuations, men are more likely than women to suppress emotional expression in certain situations. 31 , 32 A recent study reported greater gender role flexibility in women compared to men, which refers to the capacity to contextually switch between self-perceived masculine and feminine behaviours. Men experienced more negative affectivity, such as increased anxiety, self-criticism and feelings of depression when ‘code switching’ gender roles.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them even justify the selective inclusion of men to reduce putative sex differences due to hormonal alterations during the menstrual cycle (Ulrich et al, 2014(Ulrich et al, , 2018. However, the hormone-brain-cognition relationship is not as straightforward as one might think (Fine, 2010(Fine, , 2017Weigard et al, 2021), and brain differences between males and females appear trivial and population-specific based on recent accounts (Eliot et al, 2021;Rippon, 2019). In any case, to be representative of the whole population, studies should include male and female participants.…”
Section: Future Directionsmentioning
confidence: 99%